Consumer participation in maternity service development in New Zealand in the 1990s : an applied model for use in health service planning and evaluation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Health Management at Massey University - Christison, Joy Heather (Massey University, 2001)
In New Zealand throughout the 1990s, primary maternity services were the subject of considerable debate. The funders of public health services clearly signaled early in the decade that a reconfiguration of the framework for funding primary maternity services was imminent, and proceeded to involve both health professionals and consumers in discussions about the emerging new framework. The chief feature of the new framework which was implemented in 1996 was the concept of the lead maternity carer - a health professional nominated by each pregnant woman to provide and co-ordinate her care throughout the maternity episode. The body of research work which is the main focus of this thesis commenced prior to the 1996 implementation of the new framework. It took the form of a sampling frame for consumer perceptions of maternity services, with data collection periods in 1995, 1997, and 1999. Throughout this period, approximately 70 women were interviewed and over 3,000 responded to surveys. The main objectives for this sampling activity were to ascertain whether or not women's satisfaction with maternity services changed following implementation of the new framework, and to identify particular aspects of service delivery where changing levels of satisfaction were evident. In general, the new style of maternity service delivery was evaluated positively by research participants. Satisfaction with most aspects of primary maternity care remained constant and high for each data collection period. The core objectives evolved as the study progressed to include the proposition of a model for best ensuring consumer participation in health service development during periods of major change. The model consists of prospective and retrospective consultation, consumer representation during the process of detailed and final decision making, and a longitudinal sampling frame for consumer perceptions which includes pre and post implementation phases. The application of this model to the reform of primary maternity services in the 1990s enabled consumers to exert influence over the nature of the changes and to be instrumental in the validation and retention of those changes. The model proposed here has broader applicability to major reviews of other health services. Decision makers in the health arena will come to rely on mechanisms such as the model outlined in this thesis in order to plan effectively, educate and inform the public, and achieve decision making which is sanctioned by communities, against the backdrop of inevitable fiscal constraint, burgeoning demand and competing priorities for public health funding.
Keywords: Maternity services; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321215 Health care administration